The prevalence of schistosomiasis in Uganda: A nationally representative population estimate to inform control programs and water and sanitation interventions. - Natalie G Exum; Simon P S Kibira; Ronald Ssenyonga; Julien Nobili; Alexandra K Shannon; John C Ssempebwa; Edridah M Tukahebwa; Scott Radloff; Kellogg J Schwab; Fredrick E Makumbi (Public Library of Science (PLoS), 2019)
Background To improve schistosomiasis control programs in Uganda, where intestinal schistosomiasis is a widespread public health problem, a country-wide assessment of the disease prevalence among all age ranges is needed. Few studies have aimed to quantify the relationships between disease prevalence and water and sanitation characteristics across Uganda to understand the potential to interrupt disease transmission with an integrated package of interventions. Methodology/principal findings A nationally representative survey was undertaken that included a household and individual questionnaire followed by disease testing based on detection of worm antigens (circulating cathodic antigen-CCA), diagnosis and treatment. A comprehensive set of questions was asked of randomly sampled individuals, two years of age and above, to understand their water and sanitation infrastructure, open defecation behaviors, exposure to surface water bodies, and knowledge of schistosomiasis. From a set of 170 randomly sampled, geographically diverse enumeration areas, a total of 9,183 study participants were included. After adjustment with sample weights, the national prevalence of schistosomiasis was 25.6% (95% confidence interval (CI): 22.3, 29.0) with children ages two to four most at risk for the disease with 36.1% infected (95% CI: 30.1, 42.2). The defecation behaviors of an individual were more strongly associated with infection status than the household water and sanitation infrastructure, indicating the importance of incorporating behavior change into community-led total sanitation coverage. Conclusions/significance Our results highlight the importance of incorporating monitoring and evaluation data into control programs in Uganda to understand the geographic distribution of schistosomiasis prevalence outside of communities where endemicity is known to be high. The high prevalence of schistosomiasis among the youngest age group, ineligible to receive drug treatment, shows the imperative to develop a child-appropriate drug protocol that can be safely administered to preschool-aged children. Water and sanitation interventions should be considered an essential investment for elimination alongside drug treatment.